2019
DOI: 10.1088/1742-6596/1267/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Common Sensors in Industrial Robots: A Review

Abstract: The application of industrial robots has greatly promoted the development of industry in the past decades. Now with the proposal and prevalence of Industry 4.0, industrial robots are required to be more independent and intelligent to accomplish more complex and flexible tasks. The advancement of industrial robots relies on the development and progress of multiple technologies, among which sensors are the indispensable part. They can acquire abundant information to help industrial robots implement their functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Sensorial capabilities are fundamental for any robotic application. A recent overview of the most common types of sensors (e.g., visual, laser, tactile sensors, and so on) for industrial robots can be found in [38]. The growing adoption of collaborative robots is pushing toward the introduction of advanced tactile skin sensors to be attached to the robot's surface to guarantee the human operator's safety.…”
Section: New Sensors and Actuatorsmentioning
confidence: 99%
“…Sensorial capabilities are fundamental for any robotic application. A recent overview of the most common types of sensors (e.g., visual, laser, tactile sensors, and so on) for industrial robots can be found in [38]. The growing adoption of collaborative robots is pushing toward the introduction of advanced tactile skin sensors to be attached to the robot's surface to guarantee the human operator's safety.…”
Section: New Sensors and Actuatorsmentioning
confidence: 99%
“…As a side note, ultrasound sensors are widely used in robotics for obstacle recognition and tracking with high response rate and accuracy [68,69]. Recent advances in image processing and object detection algorithms have enabled optical camera sensors to be utilized for obstacle detection, especially in the area of autonomous vehicles and selfdriven cars [70,71].…”
Section: Xrmentioning
confidence: 99%
“…Some robots also have sensors for vision, taste, smell, and touch. A robot can move via actuators such as DC motors, servo motors, and stepper motors [71], and others have mechanical arms and legs [72][73][74]. Data coming from the sensors, whether analog or digital, are processed through a microcontroller.…”
Section: Overview Of Robotics and Applicationsmentioning
confidence: 99%